"Bare Truths": Poeticising Poverty, Tyranny and the Quest for Freedom in David Kerr's Tangled Tongues. Issue 1 (2nd January 2018) - Mthatiwa, Syned
Abstract : David Kerr's collection of poetry, Tangled Tongues, published in 2003, has not received much critical attention. This is not because he does not tackle critical socio-cultural and political issues relevant to their context, southern Africa, where he is based. The reason why his poetry is undervalued can partly be explained by his status as an outsider, a British expat writing about postcolonial Africa. An analysis of the poetry, however, reveals that it is a valuable achievement, both in relevance and quality. Kerr does not only engage with pressing issues in the region (like well-known local poets), but also does so in a poetic style that shows maturity and great control of his craft.